Postcolonial Analysis of AKP’s Counter-Terrorism Discourse After the June 2015 Elections - Beyribey, Tuncer (PARTECIPAZIONE E CONFLITTO, 2025)
This study examines the escalation of violence in Kurdistan by the government after the 2015 General Elections, framed as counterterrorism, and its essentialist portrayal of ’terrorists’ divorced from the historical context. It utilizes a postcolonial approach to deconstruct the ’terrorist’ subjectivity, viewing them as products of subjectification processes in peripheral spaces, serving the center’s hegemonic ambitions. The postcolonial approach exposes discourses masking internal colonialism as counterterrorism practices, seen as a dispositif for controlling these territories. The research starts from theoretical explorations of subjectification, violence, and dominance, and continues toward situating AKP’s discourse within the Kurdish Question’s historical context and its ’solution’. Focusing on June 2015 to July 2016, it illustrates the AKP’s counterterrorism discourse’s alignment with political dominance and colonial strategies. The study illuminates internal colonial relations, and counterterrorism discourse through parliamentary records, news articles, and governmental and non-governmental reports, untying the complex interplay between political violence, identity, and control.